Do Infants Attribute Moral Traits? Fourteen-Month-Olds' Expectations of Fairness Are Affected by Agents' Antisocial Actions - Surian, Luca; Ueno, Mika; Itakura, Shoji; Meristo, Marek (Frontiers in Psychology, 2018)
We investigated whether and how infants link the domains of harm, help and fairness. Fourteen-month-old infants were familiarized with a character that either helped or hindered another agent’s attempts to reach the top of a hill. Then, in the test phase they saw the helper or the hinderer carrying out an equal or an unequal distribution towards two identical recipients. Infants who saw the helper performing an unequal distribution looked longer than those who saw the helper performing an equal distribution, whereas infants who saw the hinderer performing an unequal distribution looked equally long than those who saw the hinderer performing an equal distribution. These results suggest that infants linked the hindering actions to a diminished propensity for distributive fairness. This provides support for theories that posit an early emerging ability to attribute moral traits to agents and to generate socio-moral evaluations of their actions.